2021
DOI: 10.1371/journal.pone.0258187
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis illustrates possible role of lipopolysaccharide (LPS)-induced tissue injury in nasopharyngeal carcinoma (NPC) pathogenesis

Abstract: Background Nasopharyngeal carcinoma (NPC) is a cancer of epithelial origin with a high incidence in certain populations. While NPC has a high remission rate with concomitant chemoradiation, recurrences are frequent, and the downstream morbidity of treatment is significant. Thus, it is imperative to find alternative therapies. Methods We employed a Search Tag Analyze Resource (STARGEO) platform to conduct a meta-analysis using the National Center for Biotechnology’s (NCBI) Gene Expression Omnibus (GEO) to def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The tumor tissues release a large amount of immunosuppressive factors during growth to inhibit T lymphocytes from differentiating and being mature and to induce T cells from differentiating to suppressor T cells. As a result, the percentage of T cell subsets is decreased and specific cytotoxic T lymphocytes conducive to killing EB virus are absent, leading to the treatment failure finally [ 19 , 20 ]. Therefore, improving the patients' immune function is the emphasis of treating nasopharyngeal carcinoma in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor tissues release a large amount of immunosuppressive factors during growth to inhibit T lymphocytes from differentiating and being mature and to induce T cells from differentiating to suppressor T cells. As a result, the percentage of T cell subsets is decreased and specific cytotoxic T lymphocytes conducive to killing EB virus are absent, leading to the treatment failure finally [ 19 , 20 ]. Therefore, improving the patients' immune function is the emphasis of treating nasopharyngeal carcinoma in clinic.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 is a pro-inflammatory cytokine that participates in nasopharyngeal carcinoma development and is recognized as an oncogenic factor for this tumor. High IL-1 levels are normal in nasopharyngeal carcinoma and are stimulated by T cells infiltrated in the tumor and lipopolysaccharides (LPS) [39]. In this scenario, LPS-containing Gram-negative bacteria can stimulate resident macrophages via TLR4 for TNF and IL-1 secretion, inducing cell proliferation and tumorigenesis [40].…”
Section: Discussionmentioning
confidence: 99%
“…The results of antibody staining showed that PTGS2 and MMP3 were strongly expressed in HSNC. A recent meta-analysis identified the upregulation of PTGS2, MMP1, and MMP3 in NPC tissues, shows that the maladjustment of nasal epithelial barrier and maladjusted immune response are the key components in the pathogenesis of NPC [ 22 ]. Another previous meta-analysis found that the overexpression of PTGS2 was significantly associated with a low survival rate in patients with NPC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%